Renal Cell Carcinoma in End-Stage Renal Disease: A Review and Update - Ziad M. El-Zaatari; Luan D. Truong (Biomedicines, 2022)
Renal cell carcinoma (RCC) occurring in the setting of end-stage renal disease (ESRD) shows unique clinicopathological characteristics. The two most frequent types of ESRD-associated RCC are acquired cystic kidney disease-associated renal cell carcinoma (ACKD-RCC) and clear-cell papillary renal cell carcinoma (ccpRCC). Other types of RCC also occur in ESRD, albeit with different frequencies from the non-ESRD general population. The histological features of RCC do not vary in the setting of ESRD vs. non-ESRD, yet other findings, such as multifocality and multiple tumor types, are more frequent in ESRD. Studies have generated novel and important knowledge of the etiology, epidemiology, diagnosis, treatment, immunophenotype, and molecular characteristics of ESRD-associated RCC. Knowledge of these data is important for both pathologists and other physicians who may encounter ESRD patients with RCC. This review presents a comprehensive summary and update of the literature on RCC in ESRD, with a focus on the two most frequent types, ACKD-RCC and ccpRCC.